Neuroprotective effects of Hericium erinaceus (Bull.: Fr.) Pers. against high-dose corticosterone-induced oxidative stress in PC-12 cells - Sze Yuen Lew; Siew Huah Lim; Lee Wei Lim; Kah Hui Wong (BMC, 2020)
Abstract Background Hericium erinaceus is a culinary and medicinal mushroom in Traditional Chinese Medicines. It has numerous pharmacological effects including immunomodulatory, anti-tumour, anti-microbial, anti-aging and stimulation of nerve growth factor (NGF) synthesis, but little is known about its potential role in negating the detrimental effects of oxidative stress in depression. The present study investigated the neuroprotective effects of H. erinaceus standardised aqueous extract (HESAE) against high-dose corticosterone-induced oxidative stress in rat pheochromocytoma (PC-12) cells, a cellular model mimicking depression. Methods PC-12 cells was pre-treated with HESAE for 48 h followed by 400 μM corticosterone for 24 h to induce oxidative stress. Cells in complete medium without any treatment or pre-treated with 3.125 μg/mL desipramine served as the negative and positive controls, respectively. The cell viability, lactate dehydrogenase (LDH) release, endogenous antioxidant enzyme activities, aconitase activity, mitochondrial membrane potentials (MMPs), intracellular reactive oxygen species (ROS) levels and number of apoptotic nuclei were quantified. In addition, HESAE ethanol extract was separated into fractions by chromatographic methods prior to spectroscopic analysis. Results We observed that PC-12 cells treated with high-dose corticosterone at 400 μM had decreased cell viability, reduced endogenous antioxidant enzyme activities, disrupted mitochondrial function, and increased oxidative stress and apoptosis. However, pre-treatment with HESAE ranging from 0.25 to 1 mg/mL had increased cell viability, decreased LDH release, enhanced endogenous antioxidant enzyme activities, restored MMP, attenuated intracellular ROS and protected from ROS-mediated apoptosis. The neuroprotective effects could be attributed to significant amounts of adenosine and herierin III isolated from HESAE. Conclusions HESAE demonstrated neuroprotective effects against high-dose corticosterone-induced oxidative stress in an in vitro model mimicking depression. HESAE could be a potential dietary supplement to treat depression.